Isolation of bioactive compounds with tyrosinase inhibitory activity from the methanol extract of meniran herb (Phyllanthus niruri Linn.) - Syefira Salsabila; Rika Hartati; Laode M.R. Al Muqarrabun; Nurinanda Prisky Qomaladewi; Ariranur Haniffadli; Andi Rifki Rosandy; Agus Chahyadi; Elfahmi (Institut Teknologi Bandung, 2022)
Meniran (Phyllanthus niruri L.) is a wild plant in the Euphorbiaceae family which grows in tropical climates. The plant is known to possess antioxidant activity and is rich in phenolic compounds. Since plants with high phenolic content and high antioxidant activity are known to exhibit high tyrosinase inhibitory activity, the purpose of this study is to determine the inhibitory activity of the tyrosinase enzyme by the methanol extract of meniran (P. niruri L.) and to isolate secondary metabolites from the extract and fractions which exhibit inhibitory activity against tyrosinase. The in vitro tyrosinase inhibitory activity assay was conducted using the 96-well microplate method with kojic acid as the positive control, while the separation and purification of compounds were carried out using chromatography techniques. The methanol extract and n-hexane fraction showed tyrosinase inhibitory activity with IC50 of 11.05±0.16 and 2.57±0.08 mg/ml, respectively. Three bioactive compounds were succesfully isolated from the n-hexane fraction. Based on the UV and NMR spectra, compounds 1, 2, and 3 were identified as phyllanthin, phyltetralin, and hypophyllanthin, respectively. Furthermore, phyllanthin (1) was shown to demonstrate inhibitory activity against tyrosinase with IC50 of 0.6322 mM. In conclusion, both meniran extract and phyllanthin (1) were found to exhibit inhibitory acitivity against the tyrosinase enzyme. In the future they can be candidates for the treatment against hyperpigmentation and also as an active ingredient in skincare formulations.